Effect of Lewis Number on Nonlinear Extrapolation Methods from Expanding Spherical Flames. Issue 9 (2nd September 2017) - Li, Xiaotian; Hu, Erjiang; Meng, Xin; Peng, Cheng; Lu, Xin; Huang, Zuohua
ABSTRACT: Uncertainties in measurement of the laminar flame speed and Markstein length result from various aspects, in which the methodology of extrapolation is believed to be an important factor; the present work is focusing on reducing uncertainties associated with the extrapolations. A new nonlinear extrapolation method (NL4) is proposed though further derivation of the original model, and expressed in series form. Along with the available linear model (L) and three nonlinear models (NL1, NL2, and NL3), NL4 is numerically analyzed and results indicate that it is the most accurate for mixture of Lewis number larger than unity, while NL2 is most accurate for mixture of Lewis number apparently smaller than unity. To further assess the performance of different extrapolation equations, different experimental conditions are designed and conducted using outwardly expanding spherical flame, and the results convincingly demonstrate the validity of the numerical analysis. The application of NL4 on methane/air mixture serves as a support on the accuracy and reliability of NL4, implying that NL4 may be an alternative nonlinear extrapolation method.